Perpustakaan Sekolah sebagai Sumber Informasi Guru dalam Meningkatkan Proses Pembelajaran di Madrasah Aliyah - Rifqi Zaeni Achmad Syam; Rosiana Nurwa Indah; Rahmat Fadhli (Institut Agama Islam Negeri Salatiga, 2021)
This study aims to find out the role of the school library as an information source for teachers in improving the learning process. The method used in this study is a descriptive method with a qualitative approach. Informants in this study were librarian and teachers of Madrasah Aliyah Mathla’ul Huda. Data collection techniques were carried out from December 2019 to February 2020 through observation, interviews, and documentation studies. Data analysis techniques in the form of data collection, data reduction, data presentation, and conclusion. The results of this study indicate that the information sources in the school library have been utilized by the teachers for a source to prepare learning implementation plans to improve the learning process. Based on the research results, the school library has realized its role as an information source for teachers in the learning process through library collections. In addition, 60% of the existing collections can meet the information needs of teachers. In realizing the role as an information sources, libraries experience obstacles in developing collections due to limited budgets, so that the number of books and subjects available is still lacking in meeting the needs of teachers. In addition, the library space is lacking, so it cannot accommodate large numbers of users. Therefore, the library makes various efforts to overcome, by collaborating with various related parties such as teachers and students in the selection and collections aquicition to suit their needs; cooperating with the Principal in the development of the library, especially in budget/funds.